Hubungan Tingkat Pengetahuan, Dukungan Suami, dan Sikap Ibu dengan Penggunaan Kontrasepsi IUD - Desi Satria; Chairuna Chairuna; Sri Handayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Based on data from the World Health Organization (WHO), the highest increase in contraceptive use occurred in Asian and Latin American countries, and the lowest was in Sub-Saharan Africa. In Africa from 23.6% to 28.5%, in Asia it has increased slightly from 60.9% to 61.8% while in Latin America and the Caribbean it has remained sTabel at 66.7% (WHO, 2015). This study aims to determine the relationship between the level of knowledge, husband's support, and mother's attitude with the use of IUD contraception in Sukagerak Village, OKU Regency in 2021. This study used a quantitative method with a cross sectional approach. The population in this study were active family planning participants in Sukagerak Village in 2021 with a total of 294 and a sample of 169 which was determined by the Slovyn formula and was taken using a random sampling interval system. Data analysis used univariate analysis and bivariate analysis and Chi-Square statistical test with 95% confidence level. In the bivariate analysis, it was found that there was a significant relationship between the level of knowledge, husband's support, and mother's attitude with the use of IUD contraception in Sukagerak Village, OKU Regency in 2021. This was evidenced by the results of the Chi-Square test with Pvalues of 0.015, 0.027, and 0.009 < 0.05. The conclusion is that there is a significant relationship between the level of knowledge, husband's support, and mother's attitude with the use of IUD contraception in Sukagerak Village, OKU Regency in 2021. It is recommended to health workers who are at the research site to increase counseling about IUD contraception, because there is still a lack of knowledge and interest of mothers towards IUD as an effective contraception.